IMPLEMENTASI PROGRAM SEMARAK (SENIN- KAMIS BERKARAKTER) DALAM MENINGKATKAN KARAKTER RELIGIUS HINDU SISWA SMP NEGERI 4 BANGLI: - Ni Kadek Armini; I Ketut Sudarsana; Ni Made Anggreni (JAPAM (Jurnal Pendidikan Agama), 2025)
The religious character of Hindu students plays a crucial role in shaping their personalintegrity, particularly in the face of negative social media influences that may erode their sradha anddevotion to God. This study, titled “Implementation of SEMARAK (Monday-Thursday Character)Program in Improving Hindu Religious Character of Students of SMP Negeri 4 Bangli,” aims toexplore the implementation, challenges, and implications of the SEMARAK program. Guided by B.F.Skinner’s Behaviorism Theory, Talcott Parsons’ Structural Functional Theory, and ThomasLickona’s Character Education Theory, this research employs qualitative descriptive methods withdata collected through observation, interviews, documentation, and literature review. Informantswere selected using purposive sampling. The study reveals that: (1) The SEMARAK program isimplemented consistently every Monday and Thursday through joint prayers, religious songs,spiritual reflections, and discussions on Hindu teachings; (2) The main obstacles include limitedparental involvement and the influence of social media, addressed by strengthening the role ofteachers and fostering collaboration with the community; (3) The program positively impactsstudents by enhancing their spiritual discipline, sense of gratitude, and social care, therebystrengthening their overall religious character.